If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10a + -83 = 203 Reorder the terms: -83 + 10a = 203 Solving -83 + 10a = 203 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '83' to each side of the equation. -83 + 83 + 10a = 203 + 83 Combine like terms: -83 + 83 = 0 0 + 10a = 203 + 83 10a = 203 + 83 Combine like terms: 203 + 83 = 286 10a = 286 Divide each side by '10'. a = 28.6 Simplifying a = 28.6
| X=(18+8) | | x=(x)(x) | | 34-2x=80 | | X^2-76+1380=0 | | 258=175-w | | 250=10e | | -2(2q-4)=10q-20 | | 11y+12=45 | | Sin(x)=-0.62 | | 9-7p=8 | | 09-7p=8 | | x+18+3*x=74 | | 8w+2=90 | | 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 | | 9x+-9+9x= | | f(x-3)=5x^2-x-8 | | F(x)=5x^2+6x-8 | | -10.6x+5.6x=40 | | 18x-10-6w=50 | | -5(3d+8)=35 | | -4m+2-4m+12= | | 4(u-9)= | | F(x)=5(90)-100 | | 75=5(x)-100 | | =(3x^3-7x^2+5x-9)-(7x^3-7x^2-4x+4) |